Analysis of factors influencing the performance of the ammonia converter at plant IIB of PT Pupuk Sriwidjaja - Nurisman, Enggal; Effendi, Yunita; Septiani, Nadila (Sainteks: Jurnal Sain dan Teknik, 2025)
The Ammonia converter is the primary equipment in an ammonia plant in PT Pupuk Sriwidjaja IIB where the conversion process of hydrogen and nitrogen into ammonia takes place. During this process, various constraints often arise such as changes in temperature, pressure, and the H2/N2 ratio, which can result in decreased performance and impact the conversion of the produced products. Performance evaluation of the ammonia converter is conducted to determine the condition and main factors affecting the ammonia conversion on the ammonia converter by collecting conversion data, H2/N2 ratio, temperature, and pressure. Based on the evaluation results from the data of September-November 2023, it was found that the actual average conversion of ammonia is better than the design, amounting to 20.43%. The highest conversion of ammonia is at a temperature of 399.25°C and pressure of 152.18 kg/cm2, while the lowest conversion is at a temperature of 402.17°C and pressure of 150.52 kg/cm2. Furthermore, based on statistical tests using multiple linear regression method, there are two main factors influencing the conversion of ammonia, namely temperature and pressure, while the H2/N2 ratio does not significantly affect the conversion of ammonia due to its fluctuating nature.